The impact of detailed history taking: a case report of pediatric pulmonary and hepatic hydatid disease from Ecuador - Gallegos, Camila; Vargas, Ariel; Estrella, David; Torres, Alejandra; Andrade, Carlos; Lascano, Yazmina del Carmen; Garzon-Chavez, Daniel; Aguilar, Ana Cristina (Frontiers in Pediatrics, 2024)
Background: Echinococcosis is a uncommon condition in pediatric patients, and encompasses alveolar and cystic forms, predominantly affecting the lungs and liver. Transmission occurs primarily through zoonotic means, such as the contamination of water and food by infected dog and other canid feces. Diagnosis can be challenging due to nonspecific symptoms that often mimic pneumonia. The case: A 6-year-old female patient from a rural area in Ecuador who initially presented with nonspecific symptoms indicative of pneumonia. However, further investigation into socio-environmental factors led to a diagnosis of pulmonary and hepatic hydatid disease. Conclusion: The timely and accurate diagnosis of this infectious disease enabled the patient to receive appropriate treatment and surgical intervention, leading to her complete recovery.